Edutainment Model Implementation Using If History In History Learning (Classroom Action Research at X MIPA 4 SMAN 6 Bandung) - Ramadhan, Fahmi Nur (Universitas Sebelas Maret, 2020)
This research were taken based on the low of students' understanding in historical comprehension class. The low students' understanding about history can be seen from the tendency of students that depend on textbooks that make them them cannot develop historical facts more broadly. This research tries to answer some formulation of the problem including how teachers application the learning methods to improve students' understanding of history through edutainment models using if history. The research method used in this research is the Class Action Research method with the research design model Kemmis and McTaggart that consist of the stages of planning, action, observation, and reflection. Based on the results of the research that have been done in three actions, it shows an increase in the understanding of students' history after the application of edutainment models using if history. In action I the writer obtained a score of 41.6%, action II amounted to 55.5%, in action III and IV of 100%. This increase shows that the application of edutainment models using if history is very effective to improve students' historical understanding in history learning.